Overview of Side Effects of Hormonal and Non-Hormonal Contraceptive Use Among Acceptors at Independent Midwife Practice (IMP) Iis Hilda Zicria - Maya Umul Hamidah; Ni Komang Yuni Rahyani; Gusti Ayu Tirtawati; Julieta da Costa (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2026)
Contraception is an essential method for pregnancy regulation and family planning; however, its use may cause side effects that affect user comfort and adherence. This study aimed to describe the side effects of contraceptive use among family planning acceptors at Independent Midwife Practice (IMP) of Iis Hilda Zicria. A quantitative descriptive study with a cross-sectional design was conducted from April 15 to May 8, 2025, involving 40 respondents. The results showed that 62.5% of respondents used hormonal contraceptives, predominantly injectable methods (40%), followed by oral pills (12.5%) and implants (10%). Meanwhile, 37.5% used non-hormonal contraceptives, including condoms (27.5%) and intrauterine devices (10%). Among hormonal contraceptive users, the most frequently reported side effects were weight changes (84%) and menstrual disturbances (76%). In contrast, non-hormonal contraceptive users most commonly reported changes in libido (60%), while abnormal vaginal discharge was reported only among IUD users (26.67%). Overall, non-hormonal contraceptive users experienced fewer and milder side effects compared to those using hormonal contraceptives. Healthcare providers are expected to enhance education and counseling for prospective family planning acceptors regarding the various side effects that may occur as a result of using both hormonal and non-hormonal contraceptives.